The Effects of Risedronate Therapy Combined With Vitamin D and Calcium on Biochemical Markers of Bone Turnover and Bone Mineral Density in Postmenopausal Osteoporosis - Hüsniye Koç; Hilal Sekban; Cengiz Bahadır; Nuriye Gürer; Sacide Atalay; Can Bora Önder (Galenos Yayinevi, 2004)
The aim of the study was to investigate the effects of risedronate therapy combined with vitamin D and calcium on bone mineral density(BMD) and biochemical markers of bone turnover in patients with primary postmenopausal osteoporosis. Fifty osteoporotic postmenopausal women were included in our study. All patients were given daily doses of 5 mg risodronate, 1000 mg elementary calcium and 500 IUvitamine D during 1 year study period. Dual Energy X-ray Absorbsimetry was used for the measurement of BMD's of the lumbar spine and proximal femur. In addition calcium, magnesium, phosphorus, ALP, tartarat resistant acid phosphotase (TRAP), osteocalcine levels were measured in blood and C-telopeptides(CTX1) in the urine samples . There were no significant changes in serum levels of magnesium, phosphorus and TRAP after one year of therapy. Calcium and ALP levels were lower than baseline. Osteocalcine and CTX levels were found to be decreased significantly. Lomber and proximal femur BMD's were found to be significantly increased at the end of one year. Our results demonstrated that risedronate therapy combined with calcium and vitamin D for postmenopausal primary osteoporosis results in significant increases in spinal and femur BMD's. This result was supported by changes in biochemical marker levels of bone turnover as well.